Differentiation and Transmigration of CD4 T Cells in Neuroinflammation and Autoimmunity - Sonar, Sandip Ashok; Lal, Girdhari (Frontiers in Immunology, 2017)
CD4+ T cells play a central role in orchestrating protective immunity and autoimmunity. The activation and differentiation of myelin-reactive CD4+ T cells into effector (Th1 and Th17) and regulatory (Tregs) subsets at the peripheral tissues, and their subsequent transmigration across the blood-brain barrier (BBB) into the CNS parenchyma are decisive events in the pathogenesis of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE). How the Th1, Th17 and regulatory Tregs transmigrate across the BBB into the CNS and cause CNS inflammation is not clearly understood. Studies with transgenic and gene knockout mice have unraveled that Th1, Th17 and Tregs play a critical role in the induction and resolution of neuroinflammation. However, the plasticity of these lineages and functional dichotomy of their cytokine products makes it difficult to understand what role CD4+ T cells in the peripheral lymphoid organs, endothelial BBB and the CNS parenchyma play in the CNS autoimmune response. In this review, we describe some of the recent findings that shed light on the mechanisms behind the differentiation and transmigration of CD4+ T cells across the BBB into the CNS parenchyma, and also highlight how these two processes are interconnected, which is crucial for the outcome of CNS inflammation and autoimmunity.